The integration of GIS and geophysical data in hydrocarbon exploration and exploitation - 190799 Mohd. Zukhairi Abd. Latef (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2005